Experience report: Use of gamification as a learning tool in biochemistry - Lima , Camila Daiane das Chagas de; Bortolini , Michele Fernanda; Bertocco, André Rabelo Peixoto (Seven Editora, 2023)
This study aims to describe a report of experiences on the use of gamification as a tool of learning in biochemistry to motivate and develop new skills, creativity, and oral and written communication in the academics of pharmacy. The experience reported was given by the proposal of the current educators of the discipline of biochemistry, which was based on the use of the pedagogical practice of project-based learning. Thus, the proposed challenge was to create a game for high school students, to explain the development of the disease hypercholesterolemia. This study revealed that the use of games as a teaching-learning tool is effective, attractive, and dynamic, which can be used as a pedagogical resource to increase students’ motivation and engagement and develop their cognitive skills. DOI:https://doi.org/10.56238/devopinterscie-239